Traditional and complementary medicine in Georgia: a 21st-century agenda for safe integration, regulation, and public trust - Giorgi Pkhakadze (Georgian Medical Journal, 2026)
Executive Summary: Traditional and complementary medicine (T&CM) is widely practiced in Georgia for chronic symptom relief, wellness, and self-care, with nationally documented utilisation rates reflecting both cultural embeddedness and unmet primary-care needs. The WHO Global Traditional Medicine Strategy 2025–2034, published in the Bulletin of the World Health Organization and examined in a landmark policy analysis by Dutta, represents the most authoritative framework yet adopted for embedding T&CM within evidence-based, people-centred health systems. The December 2025 Delhi Declaration, adopted at the Second WHO Global Summit on Traditional Medicine in New Delhi, reinforces that patient safety, quality assurance, and evidence generation are non-negotiable prerequisites for any integration agenda. Since 2016, Georgia has constructed an EU-aligned regulatory framework for food information, nutrition claims, and health claims on supplements, culminating in Decree N360 (2022) and Decree N227 (2024) — substantive advances toward transparent and enforceable market governance. A compliance audit of EU supplement health claims published in Foods (2026) confirms that labelling violations remain prevalent even in high-enforcement environments, underlining that regulatory architecture alone is insufficient without consistent market surveillance. National Georgian studies document high CAM utilisation, clinician education gaps, and weak institutional infrastructure; and a critical structural gap — between traditional and established medicine in communication, referral, records, and pharmacovigilance — remains insufficiently addressed globally and acutely in Georgia. This commentary synthesises the strongest available international evidence, draws lessons from India's landmark AYUSH integration model, identifies Georgia's specific implementation priorities, and proposes a coherent, time-bound, evidence-grounded policy agenda designed to position Georgia as a regional leader in responsible T&CM governance. Keywords The PDF does not contain a formal author-supplied Keywords line. Therefore, if we want keywords in OJS and at the end of the Abstract as we have done with the other papers, these should be editorial indexing terms rather than presented as original PDF keywords. I recommend: Keywords: traditional and complementary medicine; Georgia; health policy; regulation; patient safety; pharmacovigilance; food supplements; integrative medicine; public health; WHO Traditional Medicine Strategy